ICT Media to the Beginning Reading Ability of Children Aged 5-6 Years - Ekayanti, Yesi; Ananda, Addiella Fitri; Amirah, Sakinah; Sumarni, Sri; Pagarwati, Lia Dwi Ayu (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2023)
This study aims to determine the relationship between ICT-assisted learning and children's early reading skills at the Early Childhood Education Foundationin Generasi Cerdas. Beginning reading ability is the first skill that children must master when they learn to read. Utilization of telecommunication technology as part of it. In this study using descriptive qualitative method, descriptive qualitative research that applies research steps that produce descriptive data in the form of written words. The research subjects in this study were teachers, namely the process of reading development stages of children aged 5-6 years totaling 15 people. Data collection techniques obtained are observation, interviews, and documentation. From the data the results of the study of children's beginning reading ability are divided into 4 indicators that are observed, first mentioning letter symbols, second pronouncing letters, third mentioning letter sounds, and the last is stringing letters into words.